Mykhailo Zubar as a Representative of the Kharkiv School of Art History (Based on Correspondence with Dmytro Gordeyev. 1959–1964) - Sokolyuk, Lyudmyla (HUDPROM: The Ukrainian Art and Design Journal, 2024)
Mykhailo Zubar (1907–1992) was a graduate of Kharkiv Art Institute in 1929, where he received higher education as a graphic artist. His teachers were V. Yermilov and I. Padalka. He studied together with O. Dovhal, M. Kotlyarevska, M. Fradkin, B. Blank, Y. Daits and other Ukrainian graphic artists. Feeling a pull towards scientific activity, in the same 1929 he entered postgraduate studies at the Ukrainian Research Institute of the History of Material Culture. He graduated from it in 1932 and began teaching at Kharkiv Art Institute, where previously classes had been held by repressed representatives of Fedir Shmit’s school – S. Taranushenko, O. Berladina. But until the end of his life, Mykhailo Zubar remained spiritually close to the representatives of the Kharkiv school of art history, destroyed during Stalin’s times, although he tried to be very careful when working in the conditions of Soviet reality. However, during the period of “Zhdanivshchyna” he was fired from his job for “cosmopolitanism” and did not enjoy the trust of ideological bodies, also because of his connection with “Ukrainian bourgeois nationalism.” Despite of all this, M. Zubar in his pedagogical activities tried in every possible way to preserve the best traditions of the Kharkiv school of art history in the cruel conditions of the totalitarian regime, and his contribution to this matter has not yet been studied and has not received a fair assessment. However, the Central State Archive-Museum of Literature and Art of Ukraine in Kyiv preserves the correspondence of Mykhailo Zubar with Dmytro Gordeyev, a representative of the school of Fedir Shmit, who was repressed in 1933. This document was not yet identified or studied. Kharkiv resident Dmytro Gordeyev after serving his sentence in Siberia, never returned to his hometown, moving to Georgia. This unique document from the time of the Soviet totalitarianism largely reveals the spiritual worlds of Ukrainian scientific intelligentsia, which was in a state of internal rebellion to the current regime, remaining faithful to the ideals of the era of Ukrainian Executed Renaissance, the best traditions of the Kharkiv school of art history.